Late Pleistocene-Holocene paleoceanography and ventilation of the Gulf of California - Keigwin, L. D. (Journal of Oceanography, 2002)
Sediment cores collected in 1990 from the Gulf of California have been studied using stable isotope and radiocarbon techniques to reconstruct the climate and ventilation histories since the last glacial maximum. Benthic foraminiferal delta(18)O from core tops in a water depth range of 145 to 1442 m increases by about 2parts per thousand with increasing depth. This is consistent with a composite temperature profile constructed from several hydrocasts in the various gulf basins. However, the delta18O water/salinity relationship is not sufficiently linear in gulf locations or in nearby open Pacific Geochemical Ocean Sections Study (GEOSECS) stations to be useful in solving paleotemperature equations. Of the most common benthic foraminifera, only Planulina ariminensis has delta(13)C that is consistent with the measured delta(13)C of SigmaCO(2). Several cores in the depth range 500 to 900 m have the laminated Holocene and Bolling/Allerod sediments, and the nonlaminated glacial age and Younger Dryas sediments that are typical of the gulf and other locations such as Santa Barbara Basin. The best of those, Jumbo Piston Core (JPC) 56 from 818 m water depth on the western margin of Guaymas Basin, was sampled for intensive study. Oxygen isotope ratios in benthic and planktonic foraminifera show little evidence for deglacial temperature oscillations. Carbon isotope ratios are generally lower during warm epochs, but the most striking result is strongly lowered benthic and planktonic delta(13)C about 9500 years ago. This may reflect water column oxidation of locally released methane. Neither benthic delta(13)C in depth section nor paired benthic and planktonic (14)C data in JPC56 are consistent with increased intermediate water ventilation during the glacial maximum and Younger Dryas. Likewise, (14)C data from 5 pairs of foraminifera from the Okhotsk Sea fail to support better ventilation in that basin during the last glacial maximum.
554heTimes Cited:53Cited References Count:48